Phenological and distributional shifts in ichthyoplankton associated with recent warming in the northeast Pacific Ocean. (26th September 2017) - Auth, Toby D.; Daly, Elizabeth A.; Brodeur, Richard D.; Fisher, Jennifer L.
Abstract: Understanding changes in the migratory and reproductive phenology of fish stocks in relation to climate change is critical for accurate ecosystem‐based fisheries management. Relocation and changes in timing of reproduction can have dramatic effects upon the success of fish populations and throughout the food web. During anomalously warm conditions (1–4°C above normal) in the northeast Pacific Ocean during 2015–2016, we documented shifts in timing and spawning location of several pelagic fish stocks based on larval fish samples. Total larval concentrations in the northern California Current (NCC) during winter (January–March) 2015 and 2016 were the highest observed since annual collections first occurred in 1998, primarily due to increased abundances of Engraulis mordax (northern anchovy) and Sardinops sagax (Pacific sardine) larvae, which are normally summer spawning species in this region. Sardinops sagax and Merluccius productus (Pacific hake) exhibited an unprecedented early and northward spawning expansion during 2015–16. In addition, spawning duration was greatly increased for E. mordax, as the presence of larvae was observed throughout the majority of 2015–16, indicating prolonged and nearly continuous spawning of adults throughout the warm period. Larvae from all three of these species have never before been collected in the NCC as early in the year. In addition, other southern species were collected in the NCC during this period. This suggests that the spawning phenology and distribution of several ecologically and commercially important fish species dramatically and rapidly changed in response to the warming conditions occurring in 2014–2016, and could be an indication of future conditions under projected climate change. Changes in spawning timing and poleward migration of fish populations due to warmer ocean conditions or global climate change will negatively impact areas that were historically dependent on these fish, and change the food web structure of the areas that the fish move into with unforeseen consequences. Abstract : During anomalously warm conditions (1–4°C above normal) in the northeastern Pacific Ocean during 2015–2016, we documented shifts in timing and spawning location of several pelagic fish stocks based on larval fish samples. Total larval concentrations in the northern California Current (NCC) during winter (January–March) 2015 and 2016 were the highest observed since annual collections first occurred in 1998, which was primarily due to increased abundances of Engraulis mordax (northern anchovy), Sardinops sagax (Pacific sardine), and Merluccius productus (Pacific hake) larvae. Sardinops sagax and M. productus historically spawn south of the NCC region, but exhibited an unprecedented early and northward spawning expansion during 2015–16, while spawning duration was greatly increased for E. mordax, as the presence of larvae was observed throughout the majority of 2015–16.